Exposure to agricultural radio programmes and adoption of improved farming practices among farmers in Kajola local government area, Oyo state, Nigeria (2023)
Background: Radio, a powerful communication tool globally, has proven to be the most effective in the development of the agriculture sector, especially in the rural areas. Radio has been recognised as one of the most powerful mass media for the dissemination of agricultural information. Objective: The study investigated exposure to agricultural radio programmes and adoption of improved farming practices among farmers in Kajola local government area (LGA), a predominantly agricultural zone in Oyo State, Nigeria. Materials and methods: Focus group discussion (FGD) was adopted as the study design while multi-stage sampling procedure was used to select forty eight (48) discussants. Data were collected with FGD guide and thematically analyzed. Results: Finding showed that majority of the farmers were always exposed to radio agricultural programmes, although the number of years varied. Majority of the farmers confirmed that exposure to agricultural radio programmes influenced their adoption of improved farming practices. Conclusion: The study concludes that dissemination of agricultural information through radio programmes is key to the adoption of improved farming practices. The study recommends that agriculture-based research institutes should partner with broadcasting organisations, especially radio stations, in the packaging and delivery of programmes that would provide rural farmers with up-to-date information on improved agricultural practices.